FACS analysis of p24 + cells across acute and chronic cohorts. - Tine Struyve (22683295) (2025)
FACS dot plots showing the p24 KC57-FITC/28B7-APC co-staining on CD4 T cells. Red dots represent p24 + cells and frequencies of p24 + cells in CD4 T cells are depicted for each individual of the Acute UD, Acute UD + 5, Chronic UD and Chronic UD + x cohorts, accordingly to the stage of ART initiation (Fiebig II-III, Fiebig IV-V and Chronic). (TIF)